2007
DOI: 10.1124/jpet.107.130906
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Mediated Transport of the Quaternary Ammonium Neuronal Nicotinic Receptor Antagonist N,N′-Dodecylbispicolinium Dibromide at the Blood-Brain Barrier

Abstract: The quaternary ammonium compound N,NЈ-dodecyl-bispicolinium dibromide (bPiDDB) potently and selectively inhibits nicotinic receptors (nAChRs) mediating nicotine-evoked [3 H]dopamine release and decreases nicotine self-administration, suggesting that this polar, charged molecule penetrates the blood-brain barrier (BBB). This report focuses on 1) BBB penetration of bPiDDB; 2) the mechanism of permeation; and 3) comparison of bPiDDB to the cations choline and N-octylnicotinium iodide (NONI), both of which are pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…We considered bPiDDB to be an important lead candidate for further study, since it had high potency and selectivity at the nAChR mediating nicotine-evoked DA release and, like NONI, was an excellent substrate for the blood–brain barrier choline transporter (i.e., brain-bioavailable). bPiDDB exhibited the following saturable blood–brain barrier penetration parameters— V max = 4.3±1.0 nmol/min/g, K m = 5±2µM, and K d = 1.1 ±0.06 × 10 −4 ml/g—which are comparable to choline (Lockman et al, 2008). Additionally, we also found that bPiDDB diminished nicotine self-administration in proof-of-concept in vivo studies (Fig.…”
Section: Monoquaternary Ammonium Salts Derived From N-methylnicotimentioning
confidence: 99%
See 1 more Smart Citation
“…We considered bPiDDB to be an important lead candidate for further study, since it had high potency and selectivity at the nAChR mediating nicotine-evoked DA release and, like NONI, was an excellent substrate for the blood–brain barrier choline transporter (i.e., brain-bioavailable). bPiDDB exhibited the following saturable blood–brain barrier penetration parameters— V max = 4.3±1.0 nmol/min/g, K m = 5±2µM, and K d = 1.1 ±0.06 × 10 −4 ml/g—which are comparable to choline (Lockman et al, 2008). Additionally, we also found that bPiDDB diminished nicotine self-administration in proof-of-concept in vivo studies (Fig.…”
Section: Monoquaternary Ammonium Salts Derived From N-methylnicotimentioning
confidence: 99%
“…More importantly, the N-n -alkylnicotinium analogs as a group were found to have good affinity for the blood–brain barrier choline transporter, and [ 3 H]-NONI was shown to act as a substrate for this transporter in brain uptake studies in the rat. NONI exhibited the following saturable blood–brain barrier penetration parameters— V max = 603 ± 80 nmol/min/g, K m + 661± 75 µM, and K d = 7.3±3.1 × 10 −4 ml/g—compared to choline, V max = 3±0.3 nmol/ min/g, K m = 42±6µM, and K d = 1.0±0.06 × 10 −4 ml/g (Crooks et al, 2004; Lockman et al, 2008), indicating that this molecule, although cationic and polar, is brain-bioavailable. However, the general lack of selectivity of this class of analogs for α6β2* nAChRs prompted us to explore other structural modifications of the nicotine molecule.…”
Section: Monoquaternary Ammonium Salts Derived From N-methylnicotimentioning
confidence: 99%
“…Though lacking selectivity, NONI exhibited good antagonist potency at α6β2* nAChRs (IC 50 = 0.62 mM) (Crooks et al, 2004). NONI was also found to have good affinity for the BBB choline transporter (Crooks et al, 2004; Dwoskin et al, 2004; Lockman et al, 2008), suggesting good brain bioavailability due to its cationic quaternary ammonium structure.…”
Section: Discovery Of Nicotinic Receptor Antagonists As Agents Formentioning
confidence: 99%
“…The most potent among them was bPiDDB ( N , N ′-dodecane-1,12-diyl- bis -3-picolinium dibromide; Fig. 2) (IC 50 = 5 nM; Imax = 60% at α6β2*-containing nAChRs) - which had little or no affinity for either α4β2* or α7* nAChRs (Crooks et al, 2004; Dwoskin et al, 2004), and was an excellent substrate for the BBB choline transporter (Lockman et al, 2008). Pharmacokinetic studies carried out in rats treated with 14 C-bPiDDB confirmed its brain bioavailability (Albayati et al, 2008).…”
Section: Discovery Of Nicotinic Receptor Antagonists As Agents Formentioning
confidence: 99%
“…24 nature and polarity of the molecule, bPiDDB is brain bioavailable, due to its facilitated transport via the blood-brain barrier choline transporter. 25 Moreover, behavioral studies in rats showed that bPiDDB dose-dependently decreased intravenous nicotine selfadministration, but not sucrose-maintained responding, suggesting a specific inhibition of nicotine reward. 26 Taken together, bPiDDB and its analogues represent lead compounds for the development of a new class of therapeutic agents for the treatment of tobacco dependence.…”
Section: Introductionmentioning
confidence: 99%